Chemotherapy-induced senescent cancer cells engulf other cells to enhance their survival - Tonnessen-Murray, Crystal A. (J Cell Biol, 2019)
In chemotherapy-treated breast cancer, wild-type p53 preferentially induces senescence over apoptosis, resulting in a persisting cell population constituting residual disease that drives relapse and poor patient survival via the senescence-associated secretory phenotype. Understanding the properties of tumor cells that allow survival after chemotherapy treatment is paramount. Using time-lapse and confocal microscopy to observe interactions of cells in treated tumors, we show here that chemotherapy-induced senescent cells frequently engulf both neighboring senescent or nonsenescent tumor cells at a remarkable frequency. Engulfed cells are processed through the lysosome and broken down, and cells that have engulfed others obtain a survival advantage. Gene expression analysis showed a marked up-regulation of conserved macrophage-like program of engulfment in chemotherapy-induced senescent cell lines and tumors. Our data suggest compelling explanations for how senescent cells persist in dormancy, how they manage the metabolically expensive process of cytokine production that drives relapse in those tumors that respond the worst, and a function for their expanded lysosomal compartment.